Microspheres as a Unique Drug Carrier for Controlled Drug Delivery: A Review (Asian Journal of Pharmaceutics (AJP), 2023)
Comparing such systems to conventional administrative approaches, they may offer a numeral benefit.Controlled distribution of drugs can solve the problems of traditional medicine and improve medicine resources.Microspheres (MS) are generally free-flowing powders made of proteins or synthetic polymers with a particle sizeof 1–1000 mm. The literature search was accomplished using PubMed, Science direct, Google scholar, and theCochrane library to recognize appropriate scientific articles. The search terms included controlled drug deliverysystems, MS as drug carrier, advantages of MS, types of MS, importance of MS, different formulation techniquesof MS, evaluation techniques of MS, and applications of MS.